Bifidobacterium animalis KV9 and Lactobacillus vaginalis FN3 alleviated β-lactoglobulin-induced allergy by modulating dendritic cells in mice - Tian, Xiaoying; Fan, Rongbo; He, Hong; Cui, Qingyu; Liang, Xi; Liu, Qiqi; Liu, Tongjie; Lin, Kai; Zhang, Zhe; Yi, Huaxi; Gong, Piming; Zhang, Lanwei (Frontiers in Immunology, 2022)
Food allergy is a serious public health problem because of its high incidence and risk. Probiotics can induce immune regulation in patients with allergic diseases, but its mechanism is not fully clear. In this paper, β-Lactoglobulin (β- LG) sensitized mice were used as models to explore the mechanism of Bifidobacterium animals KV9 (KV9) and Lactobacillus vaginalis FN3 (FN3) on reducing allergic reactions and regulating immune cell function. The results showed that oral administration of KV9 and FN3 significantly reduced the scores of allergic symptoms, hypothermia symptoms and serum levels of β-LG-specific IgE (β-LG-sIgE), histamine and mast cell protease in allergic mice. Flow cytometry analysis of intestinal dendritic cells (DCs) showed that the proportion of CD11c+MHC-II+DCs, CD11c+CD80+DCs and CD11c+ CD86+DCs increased after KV9 and FN3 intervention, indicating that the strains induced immature DCs and decreased antigen presenting capacity of DCs. Meanwhile, the toll-like receptor 4 (TLR4)-NF-κB signaling pathway was activated in DCs. The secretion of interleukin-12(IL-12) was significantly increased and while interleukin-4 (IL-4) was decreased by DCs after KV9 and FN3 intervention, indicating that dendritic cells have the potential to promote T cell differentiation into T helper type 1 (Th1) cell. Furthermore, the proportion of CD3+CD8-IFN-γ+ T cells in the spleen increased, while CD3+CD8-IL-4+T cells decreased after oral administration of KV9 and FN3, correcting the T helper type 2 (Th2)-skewed immune. These results indicate that KV9 and FN3 reduce β-LG-induced allergic symptoms in mice, and suggest that the two potential probiotics might be used as an alternative therapeutic agent for mitigating food allergy.